Effects of Whole-Body Vibration Combined with Blood Flow Restriction and Systemic Hypoxia on Body Composition and Physical Performance in Overweight University Students - Jittima Jaisuk; Sarocha Namboonlue; Palakorn Sriwiset; Tachapon Tongterm; Arunya Buttichak; Nattha Muangritdech; Chaiyawat Namboonlue (OVS LLC, 2024)
Study purpose. This study investigated the effects of whole-body vibration (WBV) combined with blood flow restriction (BFR) and hypoxic exposure (HYP) on body composition and physical performance in overweight university students. Materials and methods. Twenty-nine male university students with overweight were divided into 3 groups: 1) whole-body vibration (WBV), 2) whole-body vibration plus blood flow restriction (WBV+BFR, 60% of occlusion pressure) and 3) whole-body vibration plus hypoxic exposure (WBV+HYP, FiO₂ = 15.8%). Training included 10 sets of intermittent WBV exercise (30-35 Hz in frequency and high amplitude) 20 min/day and 3 days/week. Body composition along with physical performance was measured before (2-3 days prior) and after (2-3 days post) an 8-week training period. Results. The results of this study were as followed, after training, the maximum strength (1RM) in the leg press and leg curl were significantly increased in the WBV+HYP group (28.31%, p = 0.016 and 13.56%, p = 0.017) compared with the WBV group (17.68% and 2.88) respectively. Similarly, the WBV+HYP group showed a substantial increase in muscle endurance in the leg extension and leg curl (28.57%, p = 0.013 and 34.38% p = 0.049) when compared to the WBV group (5.33% and 13.20%) respectively. Conclusions. Whole-body vibration combined with blood flow restriction and hypoxic exposure were effective in improving body composition and physical fitness. Performing the procedure can also be adjusted according to convenience and suitability for each individual. It is a guideline for preventing, treating, and promoting health among overweight adolescents.